Involvement of Oxidative Stress in Mitochondrial Abnormalities During the Development of Heart Disease - Dhalla, Naranjan S; Ostadal, Petr; Tappia, Paramjit S (Biomedicines, 2025)
Background: Several mitochondrial abnormalities such as defective energy production, depletion of energy stores, Ca2+ accumulation, generation of reactive oxygen species, and impaired intracellular signaling are associated with cardiac dysfunction during the development of different heart diseases. Methods: A narrative review was compiled by a search for applicable literature in MEDLINE via PubMed. Results: Mitochondria generate ATP through the processes of electron transport and oxidative phosphorylation, which is used as energy for cardiac contractile function. Mitochondria, in fact, are the key subcellular organelle for the regulation of intracellular Ca2+ concentration and are considered to serve as a buffer to maintain Ca2+ homeostasis in cardiomyocytes. However, during the development of heart disease, the excessive accumulation of intracellular Ca2+ results in mitochondria Ca2+-overload, which, in turn, impairs mitochondrial energy production and induces cardiac dysfunction. Mitochondria also generate reactive oxygen species (ROS), including superoxide anion radicals and hydroxyl radicals as well as non-radical oxidants such as hydrogen peroxide, which promote lipid peroxidation and the subsequent disturbance of Ca2+ homeostasis, cellular damage, and death. Conclusion: These observations support the view that both oxidative stress and intracellular Ca2+-overload play a critical role in mitochondrial disruption during the pathogenesis of different cardiac pathologies.
Keywords: mitochondria; oxidative stress; cell death; Ca2+-handling defects; cardiac dysfunction; heart disease